Impact of Atopic Dermatitis in Adolescents and their Parents: A French Study - Khaled Ezzedine; Jason Shourick; Stéphanie Merhand; Francesca Sampogna; Charles Taïeb (Medical Journals Sweden, 2020)
Atopic dermatitis has a negative impact on quality of life in patients and their families. However, there have been very few studies of the impact of atopic dermatitis on adolescents and their relatives. The objective of this study was to evaluate the impact of atopic dermatitis in the daily lives of adolescents between 12 and 17 years of age in the French population and to assess the burden of the disease on their families. Quality of life was measured in 399 parents of adolescents with atopic dermatitis and in the adolescents themselves. Impairment of quality of life in the adolescents was associated with disease severity. Moreover, in children aged 12-14 years, quality of life was worse with increasing age, with decreasing disease duration, and when parents had atopic dermatitis. In children aged 15-17 years quality of life was worse when the parent who answered the questionnaire was male and when the parent was <45 years old. The burden of atopic dermatitis was higher in parents of older children, in parents with children with higher disease severity, with shorter disease duration, in male parents, and in parents aged <45 years. The burden of atopic dermatitis in adolescents and their parents is considerable and should be taken into account in the management of atopic dermatitis.